Penyelesaian Kasus Khalwat melalui Peradilan Adat Aceh - Muntazar Muntazar; A. Hamid Sarong; Mohd. Din (Media Syari'ah, 2017)
Aceh Qanun No. 6 of 2014 on the Law Jinayat Article 24 Qanun said, "that jarimah seclusion under the authority of customary justice resolved according to the provisions of Qanun Aceh on life coaching and customs and / or laws and other legislation regarding the customs". With the authority granted by Qanun Jinayat, device indigenous village has a role in solving the problems jarimah seclusion, but in Article 24 of the Qanun above in accordance with the derivative or explanation states that, "Justice customary village authorities resolve the matter jarimah seclusion in the event in the village and the culprit is a resident of the village. "But in reality any problems that occur in the village remain to be resolved even if the different actors of village, even very rare actors who are the village and this shows that the explanation Articles shall not walk in the village in Aceh.